(untitled) (Comparatismi, 2019)
The Visual Narrative Grammar Theory counting the Parallel Architecture linguistic model—recently traced, the first one, by the cognitive and comics theorist Neil Cohn and, the second, by the linguist and cognitive scientist Ray Jackendoff—empirically evidence the same congenital but context modulated organizational cognitive structures founding the grammatical structure of verbal and visual languages. The identification of the visual morphology and syntax allows, then, the experimental application of the aforementioned grammar in every field of the image narration. Hence emerges the hypothesis of a dimensional counterpoint between the two communicative channels. The two-dimensional chronologically linear verbal expressions’ phrase construction is compared with the three-dimensional visual representation construct based on irregular and diachronic combination of the images. Analyzing how the visual symbols’ combination arises and to what degree it’s similar to that of verbal languages, the present study suggests that the simultaneous perception of the visual grammar elements allows an immediate, but often partial, reading of the image narration.